Influence of the selected factors on the capital structure of enterprises in the construction industry = Wpływ wybranych czynników na strukturę kapitału przedsiębiorstw sektora budowlanego - Jędrzejczak-Gas, Janina (Zielona Góra: Faculty of Economics and Management Press)
These are the issues related to shaping the capital structure of enterprises that are fundamental problems of corporate finances. Capital structure has been of interest to the researchers in the field of finance theory for over 60 years. However, the studies of the literature indicate that there was relatively little research on the capital structure and the factors shaping it in Poland. The purpose of this article is to identify and to examine the strength and the direction of the influence of the selected microeconomic factors on the capital structure of the enterprises belonging to the construction industry and quoted on the NewConnect share market.
Keywords: struktura kapitału; determinanty struktury kapitału; analiza korelacji; analiza regresji; capital structure; determinants of the capital structure; correlation analysis; regression analysis